Analysis Difficulties and Learning Strategies for Chinese Proficiency Test Level 5 Reading in Binus University - Agustian Agustian; Lydia Anggreani (Humaniora, 2014)
With the increase of Chinese learners, a number of people who attend Chinese Proficiency Test also have continued to increase. To cope with this test, Chinese Department BINUS University sets up HSK Preparation Class for its students. In this class it is found that students have some difficulties with this subject. One of them is reading part. Therefore this study was conducted through analysis of third grade students of HSK Preparation Class to find out what their problems are, to provide some suggestions, and to comment that can be used in teaching and learning process. This study is hoped to be able to provide some advice and help forteachers and students having HSK Preparation Class.